Đặc điểm biến động địa hình các cửa sông ven biển Miền Trung Việt Nam và vấn đề tiêu thoát nước lũ - Sơn, Phạm Quang (Vietnam Journal of Earth Sciences, 2002)
Characteristics of the Evolution of river mouth's topograhy and flooding di'scharge in the Central plain of Vietnam